Implementation of Integrated Marketing Communication Through The concept of Omnichannel Marketing in the Laksana Boga Campaign Marketing Program - Muluchah Fatharani Churina; Endy Gunanto Marsasi (Jurnal Informatika Ekonomi Bisnis, 2023)
Importance of equity brand in retail companies to chase enhancement advantage in finance. Retail companies must Keep going continuously and increase equity chili brand emphasizes the role important from equity brands on customers. Laksana Boga is a Center for Souvenirs and Snacks in Majenang. The company provides various souvenir products and snacks equipped with the various needs of the daily public. On souvenir products available various flavors start from salty, savory, sweet, and spicy flavors. The company needs to be optimal in system management, especially in marketing. Not optimal activity marketing is done- the company is marked with a need for consistent promotion on online channels. Study This use method studies descriptive qualitative through observation, activity interviews, a secondary data company, and collection documentation. Research results conclude that the company needs to implement Integrated Marketing Communication through Omnichannel Marketing in marketing programs Laksana Boga Campaign to maximize activity marketing on business. An increase in business revenue demonstrates the success of the marketing campaign program, i.e. 30% in the previous three periods.